1992
DOI: 10.1190/1.1443225
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fluids on grain contact stiffness and frame moduli in sedimentary rocks

Abstract: The frame moduli of sedimentary rocks are strongly influenced by the properties of the grain contacts. A modified Hertz contact theory is presented for the self consistent calculation of deformation, equilibrium separation distance (film thickness), and contact area of deformation for two spherical asperities in contact and subjected to an external load. We show that surface forces, i.e., electrostatic repulsion, Born, structural, and Van der Waals forces can be incorporated into the contact deformation proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…To remedy this situation, a number of researchers [e.g., Stoll, 1983;Chotiros, 1995;Williams, 2001;Williams et al, 2002] have studied models based on the Biot theory of poroelasticity [Biot, 1956a[Biot, , 1956b. Extensions have been made to these models to account for grain contact [Biot, 1962;Tutuncu and Sharma, 1992], stick-slip phenomena [Buckingham, 1997[Buckingham, , 2005, and ''squirt flow'' [Murphy et al, 1986;Dvorkin and Nur, 1993]. While traditional acoustical methods have had difficulty distinguishing experimentally among the predictions of these competing theories, only poroelastic media are capable of generating a macroscopic, EK response.…”
Section: Introductionmentioning
confidence: 99%
“…To remedy this situation, a number of researchers [e.g., Stoll, 1983;Chotiros, 1995;Williams, 2001;Williams et al, 2002] have studied models based on the Biot theory of poroelasticity [Biot, 1956a[Biot, , 1956b. Extensions have been made to these models to account for grain contact [Biot, 1962;Tutuncu and Sharma, 1992], stick-slip phenomena [Buckingham, 1997[Buckingham, , 2005, and ''squirt flow'' [Murphy et al, 1986;Dvorkin and Nur, 1993]. While traditional acoustical methods have had difficulty distinguishing experimentally among the predictions of these competing theories, only poroelastic media are capable of generating a macroscopic, EK response.…”
Section: Introductionmentioning
confidence: 99%
“…al. (1987), Tutuncu and Sharma (1992) Thermo-Relaxation Savage ( I 966), Kjartansson ( I 979), Amstrong ( I 980) Walsh (1968), Walsh (1969, O'Connell and Budiansky (1977) …”
Section: Proposed Attenuation Mechanisms In Granular Media and Associmentioning
confidence: 99%
“…The concept, however, has been used to successfully interpret laboratory results (Spencer, 1981;Winkler, 1985;Mavko and Jizba, 1991). Recent work by Tutuncu and Sharma (1992) has suggested that inclusion of fluid surface forces improves the estimation of attenuation.…”
Section: Squirt Fluid Flow Attenuationmentioning
confidence: 99%
“…Since the samples are dry, we know that the attenuation is not related to any wave-induced fluid motion, although it might be related in part to surface forces (see, for example, Tutuncu, -11 1992, andTutuncu andSharma, 1992). We suspect that scattering from the fractures is the dominant mechanism of the attenuation.…”
Section: A-10mentioning
confidence: 99%